Salinity tolerance of dhaincha genotypes at seed germination and seedling growth - A.K.M. Golam Sarwar (Journal of Agriculture, Food and Environment)
To evaluate the germination capability and seedling growth of dhaincha acces-sions under salt stress, the experiment was conducted at the Plant Physiology Laboratory of the Department of Crop Botany, Bangladesh Agricultural Univer-sity. The germination test was carried out in Petri dishes following two factorial CRD with four replications. Twenty-five accessions of dhaincha and three salt levels viz., 0 (control), 6 and 12 dSm–1were used as experimental treatments. The germination percentage, plant height, fresh weight and biomass yield and different stress tolerance indices were recorded and/or calculated to screen the accessions for salt tolerance. Salinity adversely affects the germination behav-iour and seedling growth descriptors of dhaincha genotypes; the seed germina-tion was relatively less affected by salt concentrations compared to other growth descriptors. A significant variation among the dhaincha accessions in response to salt stress was also observed. Only germination test was not good enough to screen germplasms for salt tolerance; however, seedling growth especially plant height and biomass accumulation could be a reliable and efficient method for screening dhaincha germplasms for salt tolerance. Based on germination behav-iour and biomass yield, five accessions viz. #5, 7, 59, 82 and 85, were selected; these accessionscan be used for further breeding programmesand/or cultivation in coastal saline-prone areas with further investigation.